Pemikiran Pendidikan Progresif Ivan Illich dalam Perspektif Filsafat Pendidikan Islam di Era Millenial - Sofa Muthohar; Fatah Syukur; Mahfud Junaedi (Islamic University of Indonesia, 2020)
This study discusses Ivan Illich’s progressive ideas from the perspective of Islamic Education Philosophy in the millennial era. This study uses a qualitative library research approach and uses content analysis. The results of this study indicate that there are several principles of learning from Ivan Illich that are in line with Islamic Education Philosophy. Firstly, the meaning of learning as knowledge sharing activities is not a school commodity. Secondly, there is equality of learning rights and without discrimination. While the principles that are considered unsuitable include two things. Firstly, the goal of Islamic education is to make people of good morals (akhlaqul karimah), while the learning objective of Ivan Illich is to realize social equality. Secondly, according to Ivan Illich, the concept of a perfect human being is human with full of hope based on effort and negates mercy (epimetheus), whereas, in Islam, a perfect person is a person of noble character (ulul albab). As for the context of the millennial generation, Ivan Illich’s progressive education will be very useful in supporting an active, creative, dynamic, and confident attitude that will be balanced if it is complemented by the spiritual nature of religiously based education.